Ants are more than just curious bystanders to some flowers—they act as significant pollinators - Das, Susmita; Das, Amlan (Frontiers in Insect Science, 2023)
Ant–plant associations are ubiquitous and highly diverse in almost all terrestrial environments, resulting in complex ecological networks. Although ant–plant mutualism is prevalent, ant-mediated pollination is uncommon, and only a few investigations have demonstrated their role in pollination. Thus, the topic of ant-mediated pollination requires revision to assess its significance in pollination biology. Ants are frequent floral visitors, but their impact on plant reproductive fitness is rarely acknowledged; nonetheless, numerous flower-visiting ants have been investigated for their involvement in promoting floral development and hybrid vigor in crops. In this study, we present a summary of the scientific literature published over the last four decades on ants’ involvement in pollination, the diversity of pollinating ants to various host plants, the ant–plant pollinating networks, and seasonal patterns of ant-mediated pollination. Ants generally forage for flowers in quest of nectar and other sustenance, and in doing so they pollinate the flowers that they encounter. This review identified the pollination networks between ants and plants at the species and family levels. Pollination is often affected by a number of aspects, including the flower’s sex, its ovary position, the inflorescence it bears, and the time of year. The available literature demonstrates that ants visit the inflorescences of the same species only to promote cross-pollination, a process known as “geitonogamy”; however, we conclude that ants may visit different inflorescences of different plants in the field. If ant pollination is the norm, there is less selection pressure to acquire self-compatibility; nonetheless, ants' cross-pollination may have caused ants to co-evolve with the pollinating flowers. This indicates that ants are more than just curious bystanders to some flowers; they act as significant pollinators.